Dysthymia in anorexia nervosa and bulimia nervosa - Carmen del Río-Sánchez (International Journal of Clinical and Health Psychology, 2008)
In this study ex post facto we have analyzed the presence of dysthymiain 155 women. Ninety three met the DSM-IV diagnostic criteria for some of the eatingdisorder (ED) types: 31 with restrictive anorexia nervosa (ANr), 31 with purging/bulimic anorexia nervosa (ANp) and 31 with purging bulimia nervosa (BNp); and 62conformed the two comparisons groups: 31 women with high risk of eating disorder(symptomatic comparative group: S-GC) and another 31 without known pathology (nonsymptomatic comparative group: NS-CG). All of them completed the Spanish versionof the MCMI-II. The results indicated that ED patients scored significantly higher onpossible dysthymic syndrome [Base Rate (BR) scores > 74], of them, 50% with ANr,60% with ANp and 63.35% with BNp. However, only 16.70% of women in high riskand 5.70% of non-pathology women showed it. These findings support that the dysthymicsyndrome is frequent in women with ED, and those with purging behaviour show aslight increase in the severity of such syndrome.